Harmonised method for impact resistance requirements of E-glass fibre/unsaturated polyester resin composite railway car bodies. (October 2018) - Önder, Asım; Robinson, Mark
Abstract: This paper shows for the first time an approach to harmonise and unify various railway standards into a single method for small object strike against rail vehicles. Emerging composite materials applications for structural parts of railway vehicles highlight the need for assessment of impact response. The objective of this work is to provide a practical and cost-effective approach for rail vehicle car bodies affected by object strikes such as flying ballast, which is a concern and restricting phenomenon for high speed rail operation. A static destructive test method combined with numerical models has been developed. High velocity impact (HVI) simulations are performed with E-glass/polyester laminates based on experiments and similarities between the two cases are highlighted. Validated numerical models are used to simulate three railway standards that are relevant to object strike in order to unify them into the proposed single method. The analysis of the energy transfer characteristics, contact forces, and impact velocity change of the projectile showed that the proposed method can be used alone instead of various existing standards, providing a significant decrease in sample size as well as avoiding the costly high-velocity impact experiments, hence resulting in substantial cost savings. Highlights: A harmonising assessment method is proposed for railway specific impact risks. The method combines destructive test and numerical model with strain rate effects. The proposed method can be used alone instead of three different standards. Impactor profile is important in some cases but not in all of them. Significant costs savings can be achieved via the proposed method.